OPTIMALISASI POTENSI PERIKANAN DESA BUNKATE MELALUI WORKSHOP PENGOLAHAN DAN PEMASARAN HASIL BUDIDAYA PERIKANAN AIR TAWAR - Miftahul Khair; Ramadhani, Aulia; Soleha, Hilalia; Siambaton, Rini Ramdani; Faqih, Farid; Kiamuddin, Moh.; Haryani, Dewina; Nurasmi, Intan; Hartiwi, Hartiwi; Redi, Muhammad (Jurnal Wicara, 2025)
Bunkate Village, Jonggat District, Central Lombok Regency, has abundant freshwater fisheries potential, especially in freshwater fisheries cultivation. However, this potential has not been managed optimally. Through a community empowerment approach, workshop activities are focused on improving the skills of village communities in processing fisheries cultivation products, as well as more effective fisheries product marketing strategies. Therefore, KKN PMD students from Mataram University initiated the Freshwater Fisheries Cultivation Results Processing and Marketing Workshop program as a solution to increase the added value of fisheries products. This activity includes training in making fish sticks as a form of product diversification and education on effective marketing strategies. The program implementation method involves observation, interviews with fish farmers, recipe formulation, and implementation of workshops attended by the local community, especially PKK mothers. The results of the activity showed that participants were enthusiastic about participating in the training and gaining new skills in processing tilapia into products with higher selling value and marketing fisheries products, which are expected to increase the income and welfare of the village community. Through this activity, it is hoped that the Bunkate Village community will be able to develop fisheries-based businesses independently and sustainably, thereby increasing the economic welfare of the village.